2001
DOI: 10.1086/317655
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis‐Associated Mortality and Estimates of Respiratory Syncytial Virus–Associated Deaths among US Children, 1979–1997

Abstract: A 1985 estimate that 4500 respiratory syncytial virus (RSV)-associated deaths occur annually among US children has not been updated using nationally representative data. Thus, 1979-1997 multiple cause-of-death records for children <5 years old listing bronchiolitis, pneumonia, or any respiratory tract disease were examined. Deaths among children associated with any respiratory disease declined from 4631 in 1979 to 2502 in 1997. During the 19-year study period, 1806 bronchiolitis-associated deaths occurred (ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
266
3
12

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(291 citation statements)
references
References 41 publications
10
266
3
12
Order By: Relevance
“…15 Use of palivizumab was generally consistent with the AAP guidelines at the time of enrollment 15,16 and published literature on potential risk factors for RSV morbidity, such as prematurity and child-care attendance, 8 and low birth weight (LBW; <2500 g). 22,23 Based on cumulative data, approximately 90% of infants were premature, 83% had LBW and 47% were enrolled in child-care or were exposed to another child in the household who attended child care. The definition of child-care attendance was left to the discretion of each site.…”
Section: Discussionmentioning
confidence: 99%
“…15 Use of palivizumab was generally consistent with the AAP guidelines at the time of enrollment 15,16 and published literature on potential risk factors for RSV morbidity, such as prematurity and child-care attendance, 8 and low birth weight (LBW; <2500 g). 22,23 Based on cumulative data, approximately 90% of infants were premature, 83% had LBW and 47% were enrolled in child-care or were exposed to another child in the household who attended child care. The definition of child-care attendance was left to the discretion of each site.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of severe RSV-associated disease varies with age and is increased by the presence of comorbidities, such as underlying lung, cardiac, and immune-compromising conditions. 2,5,6 Infants born prematurely are also at increased risk for RSV disease. In addition, previous studies suggested that American Indian (AI) and Alaska Native (AN) children and infants have higher rates of hospitalization associated with respiratory infections, compared with the general US population, with RSV being considered an important cause of these infections.…”
Section: Conclusion Rsv Infection Is One Of the Leading Causes Of Hmentioning
confidence: 99%
“…Yet, certain subpopulations including preterm and low birth weight infants are at increased risk for severe manifestations of RSV disease requiring hospitalization (24,32,40). RSV is the leading cause of bronchiolitis in infants and during the 1980s and into the mid-1990s annual RSVassociated hospitalization in the United States was estimated to be over 125,000 with nearly 500 deaths (29,35,36). Lesions frequently associated with severe RSV disease include necrotizing bronchiolitis (causing atelectasis, hyperinflation, and wheezing) and pneumonia (characterized radiographically as interstitial infiltrates, alveolar filling, and consolidation) (18).…”
Section: Introductionmentioning
confidence: 99%